Retraction Notice for "Cortical Blindness in Eclampsia" - Mahmood, Abu Kholdun Al (International Journal of Human and Health Sciences (IJHHS), 2018)
Retraction Notice: The article “Cortical Blindness in Eclampsia" DOI: http://dx.doi.org/10.31344/ijhhs.v3i1.70 was published on November 2018. There was a printing mistake in the author line which was absolutely unintentional. To avoid any misunderstanding, the Editorial Board of IJHHS retracted it on November 2018. International Journal of Human and Health Sciences Vol. 03 No. 01 January’19. Page : 26-28